Labor demand for senior employees in the context of early retirement - Yvonne Maria Marczok; Erwin Amann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
With respect to the labor market participation of the elderly in welfare states, the economic literature focuses on the incentives to the worker in the light of generous early retirement opportunities. The sociological literature on the other hand addresses the problem of low productivity of elderly in the context of occupational disability and workplace design. The economic link between supply and demand is hardly taken into account. This paper focuses on the labor demand for elderly in the context of necessary speci c investment. According to this paper, due to better perspectives on the labor market following a decrease of the incentives to retire early, e.g. by a raise in the average e ective retirement age, need not necessarily harm the elderly people. The paper thus helps to close the gap in the evaluation of pension reforms.
Keywords: D33; J26; J32; 330